The Implementation of an Experience-Based Learning Model to Enhance Student Interest and Learning Outcomes in Grade 4 at MI Insaniyah in the Physical Education Subject - Viliyus, Lambertus; Robinsar, Viliyus; Adrizal, Mohd (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
The subject of Physical Education, Sports, and Health (PJOK) holds great urgency in stimulating physical capabilities, motor agility, as well as character formation of students. However, the effectiveness of the PJOK instructional process is often hampered by the lack of students' enthusiasm for learning. In order to intervene in this problem, the Experiential Learning model is present as one of the relevant methodological solutions. This approach prioritizes internalizing concepts through direct empirical involvement so that students can learn more dynamically. This research is a research Classroom action is determined based on two indicators, namely: (1) at least 80% of students have an interest in learning in the high category, and (2) at least 80% of students achieve the KKTP score that has been set, namely 75 using observation, test and documentation techniques. This article is designed to analyze the effectiveness of the implementation of the Experiential Learning model in boosting the attention and academic performance of grade IV students of MI Insaniyah in the field of PJOK study. The results of the study confirm that the adoption of this experiential model has successfully escalated students' active involvement, interest, and learning outcomes through a series of real activities integrated with a deep reflection process.